Math, asked by usksss847, 1 year ago

solve this plz......................... ​

Attachments:

Answers

Answered by Anonymous
4

\huge\mathcal{\underline{\red{\underline{\blue{ Solution:-}}}}}

{tan}^{2}\theta - \frac{1}{{cos}^{2}\theta} + 1 = 0\\ \\</p><p>LHS = {tan}^{2}\theta - \frac{1}{{cos}^{2}\theta} + 1 \\ \\ </p><p>      = \frac{{sin}^{2}\theta}{{cos}^{2}\theta} - \frac{1}{{cos}^{2}\theta} + 1 \\ \\ </p><p>      = \frac{{sin}^{2}\theta - 1}{{cos}^{2}} + 1 \\ \\ </p><p>     = \frac{{sin}^{2}\theta - 1 + {cos}^{2}\theta}{{cos}^{2}} \\ \\</p><p>      \boxed{\red{\boxed{\pink{{sin}^{2} + {cos}^{2}= 1 }}}} \\ \\ </p><p>     = \frac{1 - 1}{{cos}^{2}} \\ \\</p><p>   = \frac{0}{{cos}^{2}} \\ \\ = 0\: RHS \\ \\ \bold{HENCE \;PROVED}

Answered by kamalpreet74
0

Answer:

hope this answers helps you....

Attachments:
Similar questions